Simplifying
3(x + -5) + -4 = 17
Reorder the terms:
3(-5 + x) + -4 = 17
(-5 * 3 + x * 3) + -4 = 17
(-15 + 3x) + -4 = 17
Reorder the terms:
-15 + -4 + 3x = 17
Combine like terms: -15 + -4 = -19
-19 + 3x = 17
Solving
-19 + 3x = 17
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '19' to each side of the equation.
-19 + 19 + 3x = 17 + 19
Combine like terms: -19 + 19 = 0
0 + 3x = 17 + 19
3x = 17 + 19
Combine like terms: 17 + 19 = 36
3x = 36
Divide each side by '3'.
x = 12
Simplifying
x = 12